Oportunidad de inserción del voluntariado en la educación universitaria en arquitectura: experiencia de dos proyectos en Lunsar, Sierra Leona (Experiencias) - Maruri Arana, Ainhoa (2024)
The central element of this work is volunteering linked to university education in Architecture. With it, this study seeks to record the benefits of including voluntary work in the field of higher formal education, specifically in the discipline of university teaching in Architecture, since they offer reflections and experiences that could improve the quality of the School, training more qualified professionals. As an example of this, two international volunteering experiences are presented in Lunsar, Sierra Leone, which have allowed to leave the national university context by putting theoretical knowledge into practice while helping the community and recognizing the potential of their knowledge and local techniques. It is concluded that the inclusion of volunteering by universities in Architecture training can represent a form of teaching innovation, introducing the student to the context of real needs, linked to the future profession.